BUSINESS IS borrow? - Santos Jiménez, Néstor (1999)
The key for a company seek funding condition is that you must have a profitable investment alternative. From a private or business perspective, the estimated profit before financing becomes economic profitability. The capital cost of any scheme of financing (debt and equity) must be equal to or greater than the economic returns needed to make the business financially viable and concrete execution condition.